2021
DOI: 10.1002/adfm.202108917
|View full text |Cite
|
Sign up to set email alerts
|

Whole‐Cell‐Mimicking Carrier‐Free Nanovaccines Amplify Immune Responses Against Cancer and Bacterial Infection

Abstract: Whole‐cell vaccines that provide broad‐spectrum antigens have been explored for recent decades. But so far, they have revealed limited success in clinical trials, possibly owing to their inefficiency in targeting immune organs and antigen‐presenting cells (APCs). Herein, a facile strategy is developed to convert the whole‐cell vaccines into the nanoscale size to promote their lymphatic migration and subsequent intracellular antigen presentation to maximize immune responses. Briefly, the study designs a multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…To prepare cell membrane, previously reported methods were used with some modification 31, 42 . Briefly, CTLL2, CTLL2-PD1 and CTLL2-PD1 treated with β-CD were collected and disrupted in hypotonic lysing buffer (pH 7.4, 20 mM Tris-HCl, 10 mM KCl, 2 mM MgCl 2 , Protease Inhibitor Cocktail) at 4 □ for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…To prepare cell membrane, previously reported methods were used with some modification 31, 42 . Briefly, CTLL2, CTLL2-PD1 and CTLL2-PD1 treated with β-CD were collected and disrupted in hypotonic lysing buffer (pH 7.4, 20 mM Tris-HCl, 10 mM KCl, 2 mM MgCl 2 , Protease Inhibitor Cocktail) at 4 □ for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…To prepare cell membrane, previously reported methods were used with some modi cations 7,51 . Brie y, CTLL2, CTLL2-PD1 and CTLL2-PD1 treated with β-CD were collected and disrupted in hypotonic lysing buffer (pH 7.4, 20 mM Tris-HCl, 10 mM KCl, 2 mM MgCl 2 , Protease Inhibitor Cocktail) at 4 ℃ for 30 min.…”
Section: Derivation Of Cell Membranementioning
confidence: 99%
“…22−24 It has been reported that particles with an intermediate size (10−100 nm in diameter) can both efficiently drain to regional draining lymph nodes and become retained there to increase the chance of antigen uptake and presentation by APCs. 25,26 Positively charged particles were also reported to be readily taken up into DCs due to the ionic attraction with the negatively charged cell membrane, which initiates efficient binding and facilitates particle internalization. 27,28 However, the effect of the particle topological structure on antigentargeted delivery has remained unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Because the uptake of antigen by DCs plays a critical role in the induction of innate and adaptive immunity, the delivery systems that not only can protect the antigens from degradation , but also can facilitate the interaction with DCs would be a promising strategy for vaccine development. The physicochemical characteristics of particles, such as the size, surface properties, rigidity, and shape, all significantly influence the in vivo trafficking and cellular internalization. It has been reported that particles with an intermediate size (10–100 nm in diameter) can both efficiently drain to regional draining lymph nodes and become retained there to increase the chance of antigen uptake and presentation by APCs. , Positively charged particles were also reported to be readily taken up into DCs due to the ionic attraction with the negatively charged cell membrane, which initiates efficient binding and facilitates particle internalization. , However, the effect of the particle topological structure on antigen-targeted delivery has remained unexplored. Thus, understanding how the topological structure influences immune responses can greatly aid in the rational design of better vaccines.…”
Section: Introductionmentioning
confidence: 99%